Develop Website-Based Emomart Using PjBL to Enhance Routing Psychomotor Skills in Students - Rizky Mutiara Citra Ayuti; Ekohariadi (Universitas Negeri Surabaya, 2025)
This study examines the influence of the website-based learning environment, Emomart, which is integrated with the Project Based Learning (PjBL) approach on improving students' psychomotor competence in routing configurations. This study adopts the Research and Development (RnD) development model with the ADDIE framework. Through the One Group Pretest-Posttest Design research design and quantitative data analysis, this study found strong empirical evidence that the learning intervention was able to significantly improve students' ability to configure the network. This research data was obtained from SMK Negeri 1 Cerme students in grade XI TKJ with a total of 30 students and the validity of research instruments, including learning media, Learning Implementation Plans (RPP), and assessment instruments, have been tested by experts (lecturers and teachers). The validation results showed the level of conformity in a row, namely, 93% (very valid), 90% (very valid), 88% (very valid), and 77% (valid). The results of high validation of the research instrument and the support of statistical tests corroborate these findings. The statistical test showed that there was a statistically significant difference between the average score of pretest = 71.39 and posttest = 81.84. The results of the Paired-Sample T-test showed a significance value of 0.000 < 0.05 indicating a significant increase in students' psychomotor competence after the learning intervention. Thus, the empirical evidence supports the alternative hypothesis, so the null hypothesis is rejected. Therefore, it is concluded that project-based learning with the support of digital platforms can be an effective strategy in improving students' technical skills in the field of computer networks.